Alcohol drinking and endometrial cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) study - Fedirko, V; Fedirko, V; Jenab, M; Rinaldi, S; Biessy, C; Allen, N; Dossus, L; Dossus, L; Onland-Moret, N; Schütze, M; Tjønneland, A; Hansen, L; et al. (2013)
Purpose: Alcohol intake may adversely affect the concentrations of endogenous sex hormones, and thus increase the risk of endometrial cancer. However, epidemiologic studies have provided conflicting results. Therefore, we investigated the association between alcohol intake and endometrial cancer risk a large, multicenter, prospective study. Methods: From 1992 through 2010, 301,051 women in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort were followed for incident endometrial cancer (n = 1382). Baseline alcohol consumption was assessed by country-specific, validated dietary questionnaires. Information on past alcohol consumption was collected by lifestyle questionnaires. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated from Cox proportional hazard models. Results: The multivariable HRs (and 95% CIs) compared with light drinkers (0.1-6 g/d) were 1.03 (0.88-1.20) for 0 g of alcohol per day at baseline, 1.01 (0.86-1.17) for 6.1-12 g/d, 1.03 (0.87-1.22) for 12.1-24 g/d, 1.07 (0.87-1.38) for 24.1-36 g/d, and 0.85 (0.61-1.18) for more than 36 g/d (ptrend = 0.77). No association was observed among former drinkers (OR, 1.28; 95% CI, 0.98-1.68 compared with light drinkers). Null associations were also found between alcohol consumption at age 20 years, lifetime pattern of alcohol drinking, and baseline alcohol intake from specific alcoholic beverages and endometrial cancer risk. Conclusions: Our findings suggest no association between alcohol intake and endometrial cancer risk. © 2013 Elsevier Inc.